Absolute and Comparative Subcutaneous Bioavailability of Ardeparin Sodium, a Low Molecular Weight Heparin - Troy, Steven; Fruncillo, Richard; Ozawa, Tsunenori; Mammen, Eberhard; Holloway, Scott; Chiang, Soong (Thrombosis and Haemostasis, 1997)
Ardeparin sodium (Normiflo®, Wyeth-Ayerst) is a low molecular weight heparin undergoing clinical evaluation as an antithrombotic agent. The objective of this study was to evaluate the absolute and comparative bioavailability of ardeparin following subcutaneous administration of three different formulations [two formulations of ardeparin at 10,000 anti-factor Xa (aXa) U/ml, but with different preservatives, and a 20,000 aXa U/ml formulation]. The study was conducted using a randomized 4-period crossover design (three subcutaneous treatments and one intravenous treatment) in 24 healthy subjects, and the pharmacokinetics of ardeparin were characterized by plasma anti-factor Ila (alia) and anti-factor Xa (aXa) activities. The mean absolute bioavailability of ardeparin based on alia activity ranged from 62% to 64% and the mean absolute bioavailability based on aXa activity ranged from 88% to 97%. Based on bioequivalence testing criteria, the three ardeparin formulations were bioequivalent.